Optimization of Natural Lip Tint Formulation Using Red Beet (Beta vulgaris L.) and Waru Leaves (Hibiscus tiliaceus L.) Extracts with Enhanced Sun Protection Factor - Yunita Dwi Asari; Devano Gothicardo; Enggar Sulistyo Wibisono; Indah Hartati; Vita Paramita (Vocational College of Universitas Diponegoro, 2025)
This study aimed to optimize the formulation of a natural lip tint utilizing red beet (Beta vulgaris L.) and Waru leaves (Hibiscus tiliaceus L.) extracts, with ZnO incorporated to enhance sun protection performance. The optimization was carried out using Response Surface Methodology (RSM), employing three independent variables—extract ratio (1:2, 1:3, 1:4), homogenization speed (5,000–12,000 rpm), and homogenization time (4–10 min)—ultimately generating 16 formulation trials. Key phytochemical responses, including betacyanin, anthocyanin, and SPF, alongside stability parameters (pH, viscosity, and density), were systematically evaluated to assess formulation performance. The optimal formulation containing ZnO (F6) produced 0.0129% betacyanin, 0.0590% anthocyanin, and an SPF value of 18.1, whereas the optimal formulation without ZnO (F15) yielded 0.0140% betacyanin, 0.0428% anthocyanin, and an SPF value of 12.7. The RSM optimization model further predicted betacyanin, anthocyanin, and SPF values of 0.0104%, 0.0593%, and 13.89 for formulations with ZnO, and 0.0109%, 0.0434%, and 11.05 for formulations without ZnO. These outcomes demonstrate that extract ratio and homogenization conditions play a critical role in determining pigment concentration, stability, and UV-protective performance, confirming the feasibility of developing a plant-based lip tint with improved functional properties through ZnO-enhanced formulation optimization.